Investigation of sleep quality and musculoskeletal pain of university students during the pandemic period: Sleep quality and pain of university students - Demirdel , Ertuğrul; Ceylan , Ali; Koçak , Hüsamettin; Güler , Mehmet Akif; Türker , Tahsin Can; Demirdel , Senem (Journal of Surgery and Medicine, 2023)
Background/Aim: The transition to distance education due to the coronavirus-19 restrictions changed the routines of university students, and physical activity and sleep status were affected due to increased computer screen use. Determining the factors affecting the sleep quality and musculoskeletal pain of university students during the pandemic period will guide the measures that can be taken to address these changes. The aim of this study was to investigate sleep quality and musculoskeletal pain of university students during the pandemic. Our research asked, “What are the factors affecting sleep quality during the pandemic period and does a difference between the musculoskeletal pain of those with good and bad sleep quality exist?” Methods: University students receiving distance education were included in this cross-sectional study. Students’ demographic characteristics, exercise habits, daily use of smart mobile devices were questioned via an online form. The Pittsburgh Sleep Quality Index was used to evaluate sleep quality, and the Cornell Musculoskeletal Discomfort Questionnaire was used to evaluate musculoskeletal pain. Sleep quality status based on regular exercise and daily mobile device usage time were compared. In addition, the musculoskeletal discomforts of the participants with good or bad sleep quality were compared. Results: Two-hundred twenty-one university students were included in the study (187 female, 34 male). Sleep quality was better in those who exercised regularly (P=0.005). Subjective sleep quality and sleep latency scores were better for those who used smart mobile devices less than 5 h a day (P=0.002 and P=0.018, respectively). Those with good sleep quality had less musculoskeletal discomfort (P<0.001). Conclusion: The findings of our study showed that increased physical inactivity and smart mobile device use during the distance education period negatively affect sleep quality. Since those with poor sleep quality have more musculoskeletal pain, we think that preventive measures, such as reducing screen time and inactivity, should be taken in distance education students to prevent health problems that may be associated with poor sleep status.